2012
DOI: 10.1089/end.2012.0055
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Treatment of a Large Prostatic Adenoma: The Laparoscopic Approach—A Systematic Review

Abstract: Even if LSP seems feasible and safe, there is still limited evidence regarding its long-term outcomes compared with OP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 40 publications
2
18
0
8
Order By: Relevance
“…The outcomes of this study corroborate the findings of three recent systematic reviews on LSP and RASP. Asimakopoulos et al reported a critical analysis of the current literature on the role of LSP [11]. Fourteen studies (11 case series and 3 comparative retrospective nonrandomized case-control studies) were included, with a total of 626 patients treated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes of this study corroborate the findings of three recent systematic reviews on LSP and RASP. Asimakopoulos et al reported a critical analysis of the current literature on the role of LSP [11]. Fourteen studies (11 case series and 3 comparative retrospective nonrandomized case-control studies) were included, with a total of 626 patients treated.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic simple prostatectomy (LSP) was first described in 2002 by Mariano et al [10] and has since been reported by several investigators with encouraging outcomes [11]. In 2008, the feasibility of robot-assisted simple prostatectomy (RASP) was demonstrated by Sotelo et al [12], and the procedure was subsequently embraced by others because of the potential advantages compared with the standard open procedure [13].…”
Section: Introductionmentioning
confidence: 99%
“…Una reciente revisión sistemática sobre AL concluye que, aunque la evidencia existente es limitada, se trata de un procedimiento factible y seguro 43 . La modificación técnica que ahora presentamos se basa en el empleo de sutura antirretorno reabsorbible, tal y como se emplea en otros procedimientos de cirugía prostática-vesical 44 , y permite también ahorro importante en el tiempo quirúrgico, facilita la estanquidad de la sutura lo que, por un lado, disminuye el escape de orina y el tiempo de sonda y, por otro, facilita el procedimiento para laparoscopistas menos experimentados.…”
Section: Discussionunclassified
“…of Pages 9 8 A. Garcia-Segui et al de interés en la disminución de la curva de aprendizaje con respecto a otras cirugías pélvicas más complejas. Sin embargo, con el desarrollo de las técnicas transuretrales con láser 45,46 y la tendencia a transformar la cirugía de la HBP en procedimiento ambulatorio y a abandonar el abordaje abdominal, parece difícil que la AL se adopte de forma masiva como cirugía estándar 43 . Posiblemente debido a la incompleta disponibilidad de equipos láser y a argumentos relacionados con los costes, la adenomectomía abierta se sigue realizando en muchos centros para tratar grandes adenomas.…”
Section: Discussionunclassified
“…Asimakopoulos ve ark. yaptıkları sistematik derlemede (22) laparoskopik basit prostatektomi ile ilgili literatürü tarayarak üçü retrospektif nonrondomize karşılaştırmalı ve on biri olgu serisi olmak üzere on dört makalenin sonuçlarını incelemişlerdir. Bu derlemede mevcut literatür bilgilerinin randomize kontrollü çalışmaların olmaması sebebiyle yetersiz olmasına rağmen laparoskopik basit prostatektominin kabul edilebilir başarı ve komplikasyon oranlarına sahip uygulanabilir bir cerrahi olduğunu belirtmişlerdir.…”
Section: Literatür Eşliğinde Laparoskopik Basit Prostatektomi Sonuçlaunclassified